Analisis Perkembangan Digitalisasi Marketing UKM Kuliner Bana Chip Lumer Dalam Perspektif Ekonomi Islam - Asri Lestari; Zuhrinal M Nawawi (Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to analyze the development of marketing digitalization for Bana Chip Lumer culinary SMEs from an Islamic economic perspective. The research was conducted by conducting interviews with the business owner, Andriani Safira, to gain insight into the use of social media and online ordering platforms in marketing Bana Chip Lumer products. The research results show that digitalization of marketing has had a positive impact on these SMEs, such as increasing product visibility, increasing sales, and expanding geographic reach. Apart from that, digital marketing also supports Islamic economic principles, such as justice, transparency and sustainability. This research provides a deeper understanding of the importance of digital marketing for culinary SMEs in achieving success and running a business in accordance with Islamic economic principles.